2002
DOI: 10.1051/0004-6361:20020860
|View full text |Cite
|
Sign up to set email alerts
|

EK Draconis: Long-term photometry on Sonneberg Sky-Patrol plates

Abstract: Abstract. We performed long-term photometry of the young solar analog EK Draconis (HD 129333) using 1030 blue-sensitive Sky-Patrol plates taken at Sonneberg Observatory from 1958 onwards. A secular dimming of 0.0057 ± 0.0008 mag/y beginning around 1975 was found. Hence, the recent trend first observed with Automatic Photoelectric Telescopes (APTs) is confirmed and traced back to the mid-seventies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 27 publications
4
19
0
Order By: Relevance
“…The results by Fröhlich et al (2002) and Järvinen et al (2005) indicated that the magnitude of EK Dra was decreasing for at least the past 45 years. This implies that a part of the surface is continuously covered with spots.…”
Section: Comparison With Long-term Photometrymentioning
confidence: 94%
See 2 more Smart Citations
“…The results by Fröhlich et al (2002) and Järvinen et al (2005) indicated that the magnitude of EK Dra was decreasing for at least the past 45 years. This implies that a part of the surface is continuously covered with spots.…”
Section: Comparison With Long-term Photometrymentioning
confidence: 94%
“…The 21 years of photometric observations show a decreasing trend in the brightness. The older measurements from Sonneberg Sky-Patrol plates (Fröhlich et al 2002) show that EK Dra was even brighter in the past. Therefore, for determining the unspotted V magnitude, the maximum V magnitude of each individual subset (from Järvinen et al 2005) was plotted against the amplitude of the subset.…”
Section: Mass Age and Lithium Abundancementioning
confidence: 99%
See 1 more Smart Citation
“…The equivalent width of Li I is about 0.2 Å, and therefore it must be relatively young. Fröhlich et al (2002, and references therein) discuss the age and activity connection.…”
Section: Introductionmentioning
confidence: 99%
“…As examples we mention that Phillips & Hartmann (1978) determined first time long-term starspot activity of BY Dra and CC Eri from Harvard plates from half a century between 1900-1950, and Fröhlich et al (2002 used the Sonneberg plate collection for studying the long-term behaviour of the solar-type single active star EK Dra and the K-giant primary of the close binary HK Lac, respectively. Vogt et al (2004) found several new variables on the Sonneberg plate collection of 34 years, most of them are early type stars from late B to A, showing slow long-term changes on the timescale of a few thousand days.…”
Section: Introductionmentioning
confidence: 99%